Electric Traction Motor Drive Modeling For Electric Karting Application Using Matlab®/Simulink® Software - D Istardi (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2009)
An electric traction motor drive for an electric karting application was modeled for efficiency studies and simulated using the MATLAB®/Simulink® software. The model includes models of a battery, power electronic converter, electric motor, and vehicles dynamic of go-karts to a typical 48 seconds track driving schedule. The losses of each component of the electric traction motor drive were modeled and simulated over the entire speed range. In the battery was also calculated the state of charge (SOC) of the battery over the driving cycle. The regenerative braking energy captured was also considered in the simulation. Finally, the overall electric traction motor drive system efficiency and energy consumed were estimated based on the individual model based efficiency and energy consumed analysis. Index Terms—Battery, electric go-kart, efficiency maps, loss modeling, and regenerative braking.